2007
DOI: 10.1007/s11120-007-9266-x
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optical responses in bacteriochlorophyll a

Abstract: Nonlinear optical responses of bacteriochlorophyll a (BChl a) were investigated by means of the three-pulse four-wave mixing (FWM) technique under the resonant excitation into the Q ( y ) band. The experimental results are explained by a theoretical model calculation including the Brownian oscillation mode of the solvent. We have determined the spectral density, which is the most important function with which to calculate optical signals. The linear absorption spectrum can be reproduced fairly well when the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Bacteriochlorophyll (BChl) a (Figure ) plays important roles in efficient energy transfer of photosynthetic systems as energy carriers in light-harvesting antennas such as Fenna–Matthews–Olson (FMO) complex, light-harvesting complex 1 (LH1) and LH2. Thus, the excited-state properties of BChl a not only in proteins but also in solutions, ,− low-temperature glasses, ,,, and polymer films , have been experimentally studied for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriochlorophyll (BChl) a (Figure ) plays important roles in efficient energy transfer of photosynthetic systems as energy carriers in light-harvesting antennas such as Fenna–Matthews–Olson (FMO) complex, light-harvesting complex 1 (LH1) and LH2. Thus, the excited-state properties of BChl a not only in proteins but also in solutions, ,− low-temperature glasses, ,,, and polymer films , have been experimentally studied for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast nonlinear responses of photosynthetic pigments have been described previously. 12,[14][15][16][17] In these studies pump-probe and transient grating ͑TG͒ spectroscopies have been widely used. 18 The most important advantage of the TG spectroscopy in comparison with the pump-probe technique is that the TG signal is background free since it is detected along the phase-matched direction of three pump pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The two lowest excited states designated as the Q x and Q y states play key roles in the primary stages of light-harvesting because they act as acceptors of energy transduction from carotenoids [11]. In contrast to the intensive studies of the Q y excited state dynamics of Bchl a [12][13][14][15][16], the dynamics of the Q x state has been poorly understood because of its extremely fast decay [17][18][19]. Previous studies have suggested that deactivation of the Q x state takes place in the range between 100~400 fs, while a detailed dynamics of the Q x state has not been sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…1(C)) was extracted from growth cells of Rhodobacter sphaeroides 2.4.1. Monomeric Bchl a was purified on a column of microcrystalline cellulose [12] and was dissolved in acetone. The absorbance was adjusted to 0.5 at excitation energy.…”
Section: Introductionmentioning
confidence: 99%